Association of Dorsal Reduction and Tip Rotation With Social Perception - Kandathil, Cherian K. (JAMA Facial Plast Surg, 2018)
IMPORTANCE: Social perception by laypersons of people who have undergone rhinoplasty primarily for cosmetic purposes has not been fully described. OBJECTIVE: To evaluate the social perception of patients who have undergone cosmetic rhinoplasty. DESIGN, SETTING, AND PARTICIPANTS: Preoperative images of 4 patients with dorsal hump and tip ptosis were selected using the Delphi method. Computer simulations of dorsal hump reduction and tip rotation, alone or in combination, were performed. Using the Qualtrics internet-based survey platform, laypersons blinded to the purpose of the study viewed randomized original and simulated images and estimated the age, approachability, perceived success, overall health, intelligence, and rated their attractiveness on a visual analog scale from 0 to 100. MAIN OUTCOMES AND MEASURES: Comparison of responses (mean [SD] score) for each of the 3 types of simulated image against the original image employing a pairwise comparison of means (Dunnett test). RESULTS: After excluding 27 (4%) invalid responses, a total of 813 respondents (593 women and 220 men) were included in the study. The mean (SD) age was 44.6 (16.2) years. A total of 628 (77%) respondents were white and the observed highest level of education was a bachelor’s degree (193 [24%]) or having attended college but without a diploma (194 [24%]). A significant age reduction (31 [10] years; 95% CI, −2.5 to 0; P = .04) and an increase in approachability (64 [22]; 95% CI, 0.7-5.8; P = .009), attractiveness (60 [22]; 95% CI, 4.0-9.4; P < .001), and health (70 [19]; 95% CI, 0.7-5.2; P = .006) for the simulation involving hump reduction was observed. When combined simulation of dorsum and tip rotation were tested, only significant increases in attractiveness (60 [23]; 95% CI, 3.6-9.0; P < .001) and health (69 [19]; 95% CI, 0.1-4.6; P = .03) were seen. No significant association was found for any of the responses when the tip alone was rotated. The Wilks λ varied slightly below 1.0 showing significant P values (P < .05) for all variance and covariance (respondent particulars). CONCLUSIONS AND RELEVANCE: Though rhinoplasty procedures for nasal cosmesis involving both the nasal dorsum and tip were perceived to make a person more attractive and healthier, these results suggest that manipulation of the dorsum is more strongly associated with perception of the nose. LEVEL OF EVIDENCE: NA